Crested wheatgrass with cattle on SGS - Gunther, Deb, photographer (Colorado State University. Libraries, 2001)
Line of crested wheatgrass between fences with cattle grazing beyond, on SGS.
Keywords: cattle; exclosures; SGS; plants; landscapes